Power Management in a Micro-grid Using Electric Vehicle - Shipra Jain, Rajesh Kr. Ahuja, Anju Gupta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The batteries in electric vehicles (EVs) may play an important role in storing potential energy. They can return excess energy back to the grid. In this way, electric vehicle batteries help in power management. To bring this vision into the picture, the necessary framework and control strategy must be designed. This study presents a framework for setting up a vehicle to grid and grid to vehicle system employing fast charging of electric vehicles. A DC test system with a fast- charging platform for interfacing electric vehicles is designed. V2G-G2V power transfer is verified through simulation. The results of the tests reveal that EV batteries, operating in G2V-V2G modes, can actively regulate power in the micro-grid.